REPRESENTASI “KOMDIS” DALAM ALTERNATE UNIVERSE OLEH FANDOM NCTZEN SEBAGAI PROSES HIPERREALITAS - Pramesti Ayu Pitaloka; Aris Arif Mundayat (Jurnal Analisa Sosiologi, 2024)
Alternate Universe (AU) is a form of fan fiction that talks about the main character (idol) in a situation and life that is made different from their original life. Twitter is one of the media used to write AUs. The majority of AUs on Twitter are presented in the form of threads containing fake chats, narratives, pictures or photos, and even videos. The blurred boundaries of reality that exist in AUs have several impacts, such as the construction of the reader's mind that their idols have the characteristics shown in the story. Many writers create role-player accounts of fictional characters to accommodate readers' imaginations. Thus, many readers cannot distinguish between the original and simulated realities. One of the most popular AUs is “Komdis” which will be the focus of this research. The researcher will examine in more depth how the relationship between AU “Komdis” in the hyperreality process and how readers represent it in social media. This research uses a qualitative method with an autoethnographic approach where the researcher is also the author of AU “Komdis”. The theory used to analyze the data findings in this research is Jean Baudrillard's hyperreality theory and Stuart Hall's representation theory. The results show that there is a double simulation where the AU itself is a simulation. Then, the readers who are simulated by “Komdis” simulate it again on social media.